Validation of the toolkit for fake news awareness in social media - Mahmood A. Al-Shareeda; Murtaja Ali Saare; Selvakumar Manickam; Shankar Karuppayah (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
Fake news has gained attention in recent years, particularly among social media users. The quick spread of fake news has been made possible by the increased usage of social media as a platform to get the most recent news and information. As a consequence, it is getting harder to distinguish between real news and fake news. This essay will outline a study that evaluated the usefulness of a toolset for identifying false news. The first hypothesis is that an increase in media literacy will result in a rise in awareness of fake news. The second theory is that fake news toolkits significantly increase students’ and working adults’ awareness of false news. On the staff of a manufacturing company and an institution, a survey was undertaken. The organization’s employees were given approximately 150 questionnaires, and 110 responses were received. The project includes the creation of a web application-a false news awareness toolkit-that will raise user awareness of fake news in terms of knowledge, behaviour, and attitude among students and workers.